The influence of the Inquiry Learning Model on students mathematical critical thinking skill - Pujiastuti, Heni; Haryadi, Rudi; Ayatullah, Fahmi (Unnes Journal of Mathematics Education, 2019)
This research is motivated by the low ability of mathematical critical thinking. So that a learning model is needed to enhance this ability. Inquiry learning model is believed to be able to improve mathematical critical thinking ability on students. This research was conducted in State Junior High School 1 Ciruas 2018/2019 academic year which aims to see the influence of inquiry learning models on students’ mathematical critical thinking ability. The research method used in this study is quasi-experimental with the non-equivalent pre-test post-test control group design. This study involved two groups consisting of the experimental and control group. The population in this study were all seventh grade students in SMPN 1 Ciruas. The sample of this study was the VII A class as the experimental group and VII E as the control group. The instrument used in this study was a mathematical critical thinking ability test. The results of the study provide the conclusion that there is an influence of inquiry learning model on students’ mathematical critical thinking ability.